# How do you write a polynomial with roots: −square root of 3, square root of 3, and 2?

A polynomial with three roots is a three-degree polynomial also known as a cubic polynomial.

## Answer: The expression for the polynomial is given as y = (x^{3} - 2x^{2} - 3x + 6).

Let's look into the solution step by step.

**Explanation:**

If a binomial has a root/zero as c, then the factor of the binomial is expressed as (x - c)

Since the roots are −√3, √3, 2, the polynomial can be expressed as:

⇒ y = (x - (-√3))(x - √3)(x - 2)

⇒ y = (x + √3)(x - √3)(x - 2)

⇒ y = (x^{2} - 3)(x - 2)

⇒ y = (x^{3} - 2x^{2} - 3x + 6)